Genome-wide analysis of the MADS-box gene family of sea buckthorn (Hippophae rhamnoides ssp. sinensis) and their potential role in floral organ development - Zhao, Jing; Xu, Yazhuo; Zhang, Zhihua; Zhao, Meng; Li, Kai; Wang, Fanhong; Sun, Kun (Frontiers in Plant Science, 2024)
Sea buckthorn (Hippophae rhamnoides ssp. sinensis) is a deciduous shrub or small tree in the Elaeagnaceae family. It is dioecious, featuring distinct structures in female and male flowers. The MADS-box gene family plays a crucial role in flower development and differentiation of floral organs in plants. However, systematic information on the MADS-box family in sea buckthorn is currently lacking. This study presents a genome-wide survey and expression profile of the MADS-box family of sea buckthorn. We identified 92 MADS-box genes in the H. rhamnoides ssp. Sinensis genome. These genes are distributed across 12 chromosomes and classified into Type I (42 genes) and Type II (50 genes). Based on the FPKM values in the transcriptome data, the expression profiles of HrMADS genes in male and female flowers of sea buckthorn showed that most Type II genes had higher expression levels than Type I genes. This suggesting that Type II HrMADS may play a more significant role in sea buckthorn flower development. Using the phylogenetic relationship between sea buckthorn and Arabidopsis thaliana, the ABCDE model genes of sea buckthorn were identified and some ABCDE model-related genes were selected for qRT-PCR analysis in sea buckthorn flowers and floral organs. Four B-type genes may be involved in the identity determination of floral organs in male flowers, and D-type genes may be involved in pistil development. It is hypothesized that ABCDE model genes may play an important role in the identity of sea buckthorn floral organs. This study analyzed the role of MADS-box gene family in the development of flower organs in sea buckthorn, which provides an important theoretical basis for understanding the regulatory mechanism of sex differentiation in sea buckthorn.